(untitled) (Journal of Parents and Teachers, 2014)
The grades are crucial because they are the main means of communication between the family and the school and because it is the way to know the progress of students. To evaluate, a report is prepared and filled with truthful information. Finally, the report card comes home. In addition to this explanation, the article offers other important ideas to consider during the evaluation process, such as the parent interview.